Effect of hypobaric hypoxia on heart rate variability during exercise: a pilot field study - Zupet, P.; Princi, T.; Finderle, Z. (European Journal of Applied Physiology, 2009)
The influence of hypoxia on heart rate variability (HRV) has been studied under resting conditions with mixed results. Differences have been found in physiological responses to normobaric versus hypobaric hypoxia. Our aim was to study the influence of hypobaric hypoxia on HRV during physical exercise to determine whether HRV changes due to the exercise-induced heart rate (HR) increase or whether hypoxia itself exerts an influence. We tested nine healthy non-acclimatised white males (age = 43 ± 7 years) at 400 and 4,200 m during exercises. At 400 m HRV was measured at 50% and 75% maximal oxygen uptake (VO2 max). At 4,200 m HR was kept equal as during exercise at 400 m by adjusting the intensity of step testing. The Poincaré plot as a non-linear method of HRV analysis was used, where the shape of the ellipse depending on HRV is expressed by two parameters, SD1 and SD2 (correlating to parasympathetic activity and both sympathetic and parasympathetic activity, respectively). We established a decrease in SD2 and an insignificant decrease in SD1 at medium HR at 4,200 m compared to 400 m. Both parameters showed similar tendencies during high-intensity exercise. Our results indicate that hypobaric hypoxia itself exerts an influence on HRV at a moderate HR.